About the Fundamental Standards of Nutrition, Food Security, and Food Sovereignty (Global Journal of Medical Research, 2025)
Today an estimated one billion people are hungry and undernourished with detrimental effects on the growth and learning abilities of children and on the ability of adults to lead fully productive lives Most of these people are in parts of the world where the food available to them is often contaminated or adulterated increasing the risk of foodborne illness and pandemic gastrointestinal illnesses Today s reality highlights the existential need for developing countries to improve food safety and quality measures and the challenges associated with meeting these needs This review article addresses the need to improve food quality and safety systems in developing countries in the context of food security public health and international trade and provides evidence and tools to address these challenges using new approaches to capacity building and providing technical assistance on food and nutrition technologies
Keywords: “malnutrition”